Low profilin 1 serum levels are associated with diabetes, family history and multivessel lesions in patients with coronary artery disease - Paszek, Elżbieta; Zajdel, Wojciech; Plens, Krzysztof; Żmudka, Krzysztof; Legutko, Jacek; Kleczyński, Paweł (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Atherosclerosis, underlying coronary artery disease (CAD), is best characterized as a low-grade inflammatory condition, where cholesterol particles – mostly oxidized low-density lipoproteins (ox-LDL) – infiltrating the vessel wall act as an antigen and initiate an inflammatory response [1]. This approach has been explored for many years now but does not allow for a full understanding of the disease. Recently, the actin cytoskeleton and associated regulatory proteins have been gaining attention as contributors to the pathophysiology of CAD [2]. Among these, profilin 1 (Pfn1) is an emerging player in the field [3, 4]. Research showed that Pfn1 was overexpressed in atherosclerotic lesions in comparison to the healthy vessel wall [5]. In mice a deletion of one copy of the PFN1 gene increased the production of nitric oxide, lowered the expression of adhesion molecules and hindered macrophage infiltration, thereby protecting against atherosclerosis [6]. In diabetic atherosclerosis models, Pfn1 was overexpressed in endothelial cells exposed to advanced glycation end-products, accompanied by hallmarks of endothelial dysfunction [7]. Pfn1 was also implicated in the pathophysiology of acute coronary syndromes. It was found within thrombi retrieved from culprit arteries and correlated with symptom duration, as well as final Thrombolysis in Myocardial Infarction flow [8, 9].